Racial Crime Stereotypes and Offender Juvenility: Comparing Public Views About Youth-Specific and Nonyouth-Specific Sanctions. (October 2014) - Pickett, Justin T.; Welch, Kelly; Chiricos, Ted; Gertz, Marc
Recent theoretical advancements of the racial threat model of punitiveness suggest that because youthful offending has driven crime trends in recent decades, and because racially exclusive conceptions of childhood have historically structured public opinion on juvenile justice, Black criminal stereotypes may be especially consequential for attitudes toward juvenile punishments. Building on this work, the current study uses national survey data to examine whether the strength of the relationship between Black criminal stereotypes and support for punitive policies varies according to whether punishments are targeted toward juvenile delinquents or criminals in general. We find that Black criminal stereotypes are positively associated with punitive attitudes and that the magnitude of this effect is statistically identical in the cases of youth-specific and nonyouth-specific sanctions. Thus, the results suggest that racialized support for punitive crime policies is not influenced by the juvenility of the offender.